Flexible aqueous ammonium-ion full cell with high rate capability and long cycle life. (February 2020) - Li, Hui; Yang, Jie; Cheng, Jianli; He, Tao; Wang, Bin
Abstract: Aqueous full cell based on non-metal NH4 + ions redox reactions has been reported recently owing to NH4 + ions as charge carriers with advantages of abundant resources, light weight, eco-friendly and fast diffusion capability. However, the exploration of NH4 -ions full cell is still in its infancy. Despite the aforementioned unique properties of the aqueous NH4 -ions full cell, there is almost no reported about the flexible NH4 -ions full cell so far. Developing novel electrodes with highly reversible NH4 -ions accommodation capability underlies the construction of high-performance full cells. Here, we first demonstrate a novel flexible aqueous ammonium-ion full cell with high rate capability and long cycle life consisted of urchin-like NH4 V4 O10 coated on carbon fiber cathodes and polyaniline nanorods grown on carbon fiber anodes in (NH4 )2 SO4 aqueous solution. A high specific capacity up to 167 mA h g −1 at a current density of 0.1 A g −1, excellent rate capability with a specific capacity of 54 mA h g −1 at 1 A g −1 and an ultralong cycle life with a high capacity retention are achieved. Meanwhile, the NH4 -ion full cell shows good flexibility with well-maintained electrochemical performances at different deformation states. This work may shed a light on developing flexible aqueous NH4 -ion cells. Graphical abstract: Image 1 Highlights: Flexible fiber-shaped aqueous NH4 -ion full cells are fabricated for the first time. The NH4 -ion full cells exhibit a high specific capacity and excellent rate capability. Energy storage devices based on non-metal-ions redox reactions are promising.